Navigating the Tension Between National Interests and Global Cooperation: Contemporary Governance Challenges in Defense and Security - Ernalem Bangun; Otto Trengginas Setiawan; Pujo Widodo; Yumasdaleni Yumasdaleni (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2025)
In the contemporary landscape of global governance, persistent tensions exist between national strategic interests and the urgent need for international collaboration. Major global challenges such as climate change, digital security, and inequality demand coordinated responses across nations. Yet, state actors often prioritize sovereign goals, creating friction in efforts toward collective action. This study examines these tensions and evaluates the relevance of international institutions like the United Nations (UN) and World Trade Organization (WTO) amid shifting power dynamics, rising nationalism, and protectionist policies. Employing a qualitative descriptive approach through literature review, the research analyzes how the fragmentation of global governance undermines institutional effectiveness. The study emphasizes that developing countries are gaining influence due to demographic shifts and economic growth, highlighting the need for inclusive decision-making processes. Findings indicate a legitimacy crisis among international institutions struggling to adapt to these geopolitical shifts. The study concludes that overcoming structural polarization requires balancing national interests with cooperative global strategies. Strengthening institutional capacity and embracing inclusive policies are essential for ensuring long-term security, stability, and sustainability in an increasingly interconnected world.